2020
DOI: 10.1242/jcs.232405
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, motility and matrix-degrading gene expression changes in CSF-1-induced mouse macrophage differentiation

Abstract: Migratory macrophages play critical roles in tissue development, homeostasis and disease so it is important to understand how their migration machinery is regulated. Whole transcriptome sequencing revealed that CSF-1-stimulated differentiation of bone marrow-derived precursors into mature macrophages is accompanied by widespread, profound changes in expression of genes regulating adhesion, actin cytoskeletal remodeling and extracellular matrix degradation. Significantly altered expression of almost 40% of adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…To further validate our findings, macrophages from P3 versus P4 were analyzed in GO pathways. Consistent with the previous report that showed the development of an adherent phenotype of BMDMs upon exposure to increasing doses of M-CSF [40], the GO pathways from our data also manifested the cells from P4 versus P3 fractions in the regulation of cell motility, cell adhesion and cell migration (Figure 6D). Those higher activities indicates faithfully the M2-like phenotypes of macrophages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To further validate our findings, macrophages from P3 versus P4 were analyzed in GO pathways. Consistent with the previous report that showed the development of an adherent phenotype of BMDMs upon exposure to increasing doses of M-CSF [40], the GO pathways from our data also manifested the cells from P4 versus P3 fractions in the regulation of cell motility, cell adhesion and cell migration (Figure 6D). Those higher activities indicates faithfully the M2-like phenotypes of macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the preponderance of extracellular matrix related makers in the upregulated gene set, the top downregulated genes in P4 macrophages encoded proteins with disparate functions, including biological process (CLEC4A1, ERMARD), glycolytic process (ENO1B), metabolic process (DYNLT1B, ATP6V0C-PS2, FUNDC2), cell cycle process (CCNA2, PAGR1A, CDK20, HJURP, DLGAP5), mRNA processing (SRSF7), cellular response (IFI209), response to virus (OAS1A, EVI2), defense response (CCR5, HIST1H2BK) and unknown (BCC003331, CYP4F16). Consistent with previous study [40], we found that the top upregulated Gene Ontology (GO) pathways regulated cell motility, cell adhesion and cell migration mostly (Figure 5D) and the top downregulated GO pathways regulated metabolism, cell cycle and cellular response, and so forth. (Figure 5E).…”
Section: Endogenous Expression Of Csf-1 Was Augmented In M2 Macrophages After Withholding Of M-csf Supplementsupporting
confidence: 91%
“…While we cannot formally exclude legacy activity of RK20449 against FGR, our previous genetic observations in Hck KO hosts argue that the antitumor effects conferred by RK20449 arise primarily from limiting HCK activity ( 3 ). We also note that FGR is less abundant than HCK in myeloid cells and down-regulated along the monocyte-macrophage differentiation pathway ( 34 ).…”
Section: Discussionmentioning
confidence: 95%
“…Both membrane protein integrity and cell viability during dissociation are critical for successful downstream biological studies ( 3 , 4 ), including flow cytometry and single cell RNA sequencing. Besides, cell adhesion characteristics vary with macrophage maturation/polarization ( 5 , 6 ). Therefore, it is essential to determine the appropriate dissociation methods for different macrophage populations.…”
Section: Introductionmentioning
confidence: 99%